The Theory of Resonant Cosmic Ray–driven Instabilities—Growth and Saturation of Single Modes - Rouven Lemmerz; Mohamad Shalaby; Christoph Pfrommer; Timon Thomas (The Astrophysical Journal)
Cosmic-ray (CR) feedback is critical for galaxy formation as CRs drive galactic winds, regularize star formation in galaxies, and escape from active galactic nuclei to heat the cooling cores of galaxy clusters. The feedback strength of CRs depends on their coupling to the background plasma and, as such, on the effective CR transport speed. Traditionally, this has been hypothesized to depend on the balance between the wave growth of CR-driven instabilities and their damping. Here, we study the physics of CR-driven instabilities from first principles, starting from a gyrotropic distribution of CR ions that stream along a background magnetic field. We develop a theory of the underlying processes that organize the particles’ orbits and in particular their gyrophases, which provides an intuitive physical picture of (i) wave growth as the CR gyrophases start to bunch up lopsidedly toward the local wave magnetic field, (ii) instability saturation as a result of CRs overtaking the wave and damping its amplitude without isotropizing CRs in the wave frame, and (iii) CR backreaction onto the unstable plasma waves as the CR gyrophases follow a pendulum motion around the wave magnetic field. Using our new fluid-particle-in-cell code fluid-SHARP, we validate our theory on the evolution and excitation of individual unstable modes, such as forward- and backward-propagating Alfvén and whistler waves. We show that these kinetic simulations support our theoretical considerations, thus potentially foreshadowing a revision of the theory of CR transport in galaxies and galaxy clusters.